2004
DOI: 10.1074/jbc.m305804200
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factors Regulate the Lama1 Gene Encoding the Laminin α1 Chain

Abstract: Laminin-1 (␣1␤1␥1), a basement membrane (BM) constituent, has been associated with differentiation processes and also with malignant progression. In the intestinal tissue, the ␣1 chain is expressed and secreted in the subepithelial BM during the developmental period; in the adult rodent tissue, it is restricted to the BM of the dividing cells. To understand how laminin ␣1 chain expression is regulated, we cloned and characterized a 2-kb promoter region of the Lama1 mouse gene. Analysis of the promoter was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…A potential reason for this competing effect is due to physical competition of the two proteins in binding to a cognate sequence in the KLF4 promoter [13]. A similar competing effect between KLF4 and KLF5 in the transcription of several other genes has also been described, including those encoding smooth muscle α-actin [14] and laminin-1 [15].…”
Section: Klf4 and Klf5 Bind To Similar Dna Sequences But Exert Opposimentioning
confidence: 90%
“…A potential reason for this competing effect is due to physical competition of the two proteins in binding to a cognate sequence in the KLF4 promoter [13]. A similar competing effect between KLF4 and KLF5 in the transcription of several other genes has also been described, including those encoding smooth muscle α-actin [14] and laminin-1 [15].…”
Section: Klf4 and Klf5 Bind To Similar Dna Sequences But Exert Opposimentioning
confidence: 90%
“…Alternatively, it is possible that the same enhancer controls both sites of expression, because we showed that the pre-somitic mesoderm is not competent to respond to Shh signalling owing to the absence of Gli proteins (Borycki et al, 2000;McDermott et al, 2005). Two studies have unveiled a putative promoter or enhancer region upstream of exon 1 of Lama1 (Niimi et al, 2003;Piccinni et al, 2004). Further work is required to establish whether Shh-Gli signalling affects this transcriptional activity directly.…”
Section: Differential Requirement For Gli2 and Gli3 In Myotomal Basemmentioning
confidence: 94%
“…Although at least some of the functions of KLF4 and KLF6 seem to be similar, KLF5 has been proposed to have complementary functions to those of KLF4 (REF. 14), in that they have opposing effects on the expression of their shared target genes [64][65][66] . It is not entirely clear whether the settings in which KLF4 functions as an oncogene are similar to those in which KLF5 functions as a tumour suppressor, or vice versa.…”
Section: Klf4 As An Oncogenementioning
confidence: 99%